YORUM: BİRİNCİ YILINDA ANAYASA MAHKEMESİNE BİREYSEL BAŞVURU KARARLARININ ANALİZİ - (:unkn) unknown (My University, 2014)
İncelemede genel olarak Profesör Sibel İncoğlu’nun metni esas alınmak suretiyle, Anayasa Mahkemesinin ilk bireysel başvuru kararla- rının genel özellikleri ve sonuçları incelenmeye çalışılmıştır. Burada öncelikle Anayasa Mahkemesinin Anayasa-İnsan Hakları Avrupa Söz- leşmesi ilişkilerine dair tutumu değerlendirilmiş; ardından da Anayasa Mahkemesinin diğer mahkemelerle olan ilişkilerine dair anayasal ve yasal düzenlemeler üzerinde durulmuştur.

On the basis of Professor Sibel İnceoğlu’s comments on Constitutional Court rulings, this paper attempts to evaluate the general characteristics and consequences of the recent judgments of the Constitutional Court in response to individual applications. In the first part of the paper, the attitude of Constitutional Court regarding the relations between the Constitution and the European Convention on Human Rights is examined. The second part relates to the constitutional and legal rulings, which indicate the absence of superior/subordinate relationship between the Constitutional Court and other national Supreme Courts.
COMMENT: INDIVIDUAL APPLICATION BEFORE THE TURKISH CONSTITUTIONAL COURT: AN ANALYSIS OF THE CASES IN ITS FIRST YEAR
Keywords: Uluslararası İlişkiler; Hukuk